VOCABULARY ASSESMENT STRATEGY - Wanrika Tampubolon; Feronika Sinamo; Erikson Saragih (IKIP Siliwangi, 2022)
This research aims to find out the vocabulary assessment strategy used by teachers in assessing students' vocabulary in secondary schools and how the results of applying the vocabulary assessment strategy are to students' vocabulary skills. This research uses qualitative descriptive the data collection uses a questionnaire included in the google form and distributed to 10 English teachers from various schools in North Sumatera. From this research, it was found the vocabulary assessment strategy used by teachers during the examination was to match the word (40%), multiple-choice (30%), fill the blank (20%), and define the word (10%). The vocabulary practice strategies used are memorizing, puzzle games, paper forms, shorting-guided words, reading comprehension, asking and answering methods, conversation, oral tests, and written tests. This research concludes that the vocabulary assessment strategy is used very helpful for students to achieve the targets and 60% satisfactory for students' knowledge and 40% is moderate. Keywords: Vocabulary, Assesment, Strategy